Design & Capacity Analysis of Flexible Pavement - Thakur, Puneet (My University, 2022)
Flexible pavement is the most commonly type of pavement used in construction of roads. Design and analysis of flexible pavement of Delhi – Katra expressway is done. The allowable horizontal and vertical strain is compared with actual stain using IIT PAVE software. Capacity analysis of phase II of Delhi – Katra expressway is done as per IRC : SP 99 -2013. Capacity analysis is fundamental to the planning, design and operation of National Highways and provides among other things , the basis for determining the carriageway width to be provided at any point of time with respect to the volume and composition of traffic .It is an important tool for evaluation of the investment needed for the future construction and improvements and for working out priorities of road projects.
Keywords: Capacity analysis; CBR test; Delhi-Katra expressway